Analisis Cross Section Pada Perusahaan Sektor Tambang Yang Terdaftar Di Bursa Efek Indonesia - Putri Nugraheni; Nadia Dwi Pratiwi; Fatika Rahma Fina; Badzlina Chaerani Putri; Cholis Hidayati (BADAN PENERBIT STIEPARI PRESS, 2024)
The mining sector has a vital role in the country's economic system. This analysis is to analyze the financial performance of companies operating in the mining sector listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. The method used for cross section analysis takes secondary data from the company's financial reports. Analysis variables: Liquidity Ratio, Activity Ratio, Solvency Ratio, and Profitability Ratio. The research results show that the financial performance of the company with this cross-section analysis, PT Aneka Tambang Tbk emerged as the leader in the mining sector during the 2020-2022 period. This advantage shows the resilience of the company's management strategy and operational capabilities in facing challenges in the market and external environment.